2004
DOI: 10.1038/sj.bjp.0705662
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of M826, a reversible caspase‐3 inhibitor, in the rat malonate model of Huntington's disease

Abstract: 1 Caspases, key enzymes in the apoptosis pathway, have been detected in the brain of HD patients and in animal models of the disease. In the present study, we investigated the neuroprotective properties of a new, reversible, caspase-3-specific inhibitor,, in a rat malonate model of HD. 2 Pharmacokinetic and autoradiography studies after intrastriatal (i.str.) injection of 1.5 nmol of M826 or its tritiated analogue [ 3 H]M826 indicated that the compound diffused within the entire striatum. The elimination half-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 41 publications
3
42
0
Order By: Relevance
“…M-826, a small reversible caspase-3 inhibitor, blocked brain tissue damage in an animal model of hypoxia-ischemia when injected intracerebroventricularly 2 h after ligation (Han et al, 2002). In a mouse model of Huntington's disease, M-826 also prevented cell death of striatal neurons (Toulmond et al, 2004). The broad spectrum caspase inhibitor M-920 as well as the caspase 3-specific inhibitor M-791 decreased lymphocyte apoptosis in thymus and spleen of mice subjected to polymicrobial sepsis induced by cecal ligation-puncture and rescued 80 to 90% of animals from lethal septic shock (Hotchkiss et al, 2000).…”
Section: Fischer and Schulze-osthoffmentioning
confidence: 99%
“…M-826, a small reversible caspase-3 inhibitor, blocked brain tissue damage in an animal model of hypoxia-ischemia when injected intracerebroventricularly 2 h after ligation (Han et al, 2002). In a mouse model of Huntington's disease, M-826 also prevented cell death of striatal neurons (Toulmond et al, 2004). The broad spectrum caspase inhibitor M-920 as well as the caspase 3-specific inhibitor M-791 decreased lymphocyte apoptosis in thymus and spleen of mice subjected to polymicrobial sepsis induced by cecal ligation-puncture and rescued 80 to 90% of animals from lethal septic shock (Hotchkiss et al, 2000).…”
Section: Fischer and Schulze-osthoffmentioning
confidence: 99%
“…This is the model of striatal injury generated by unilateral injections of malonate, another complex II inhibitor that, in contrast with 3-nitropropionic acid, produces cell death through the activation of apoptotic pathways [it activates NMDA receptors and caspase-3 (66)]. Using this model, we found neuroprotection when rats were administered with a selective CB 2 receptor agonist, but not with a selective CB 1 receptor agonist or with an antioxidant cannabinoid with no affinity for both receptor types as CBD (15).…”
Section: Cannabinoids and Neuroprotection In Huntington's Diseasementioning
confidence: 99%
“…Recently, Toulmond et al 75 showed that an inhibition of caspase-3 activity by the reversible caspase-3 inhibitor (M-826) results in a significant reduction in neuronal death after striatal lesions in adult rats.…”
Section: Caspase-3 In Neurological Diseasementioning
confidence: 99%